Clinical Review of Antidiabetic Drugs: Implications for Type 2 Diabetes Mellitus Management - Chaudhury, Arun; Duvoor, Chitharanjan; Reddy Dendi, Vijaya Sena; Kraleti, Shashank; Chada, Aditya; Ravilla, Rahul; Marco, Asween; Shekhawat, Nawal Singh; Montales, Maria Theresa; Kuriakose, Kevin; Sasapu, Appalanaidu; Beebe, Alexandria; et al. (Frontiers in Endocrinology, 2017)
Type 2 diabetes mellitus (T2DM) is a global pandemic, as evident from the global cartographic picture of diabetes by the International Diabetes Federation (http://www.diabetesatlas.org/). Diabetes mellitus is a chronic, progressive, incompletely understood metabolic condition chiefly characterized by hyperglycemia. Impaired insulin secretion, resistance to tissue actions of insulin, or a combination of both are thought to be the commonest reasons contributing to the pathophysiology of T2DM, a spectrum of disease originally arising from tissue insulin resistance and gradually progressing to a state characterized by complete loss of secretory activity of the beta cells of the pancreas. T2DM is a major contributor to the very large rise in the rate of non-communicable diseases affecting developed as well as developing nations. In this mini review, we endeavor to outline the current management principles, including the spectrum of medications that are currently used for pharmacologic management, for lowering the elevated blood glucose in T2DM.